Stability of Morphine, Codeine, and 6‐Acetylmorphine in Blood at Different Sampling and Storage Conditions. Issue 2 (21st November 2013) - Papoutsis, Ioannis; Nikolaou, Panagiota; Pistos, Constantinos; Dona, Artemisia; Stefanidou, Maria; Spiliopoulou, Chara; Athanaselis, Sotirios
Abstract The stability of drugs in biological specimens is a major concern during the evaluation of the toxicological results. The stability of morphine, codeine, and 6‐acetyl‐morphine in blood was studied after different sampling conditions: (i) in glass, polypropylene or polystyrene tubes, (ii) with addition of dipotassium ethylene diamine tetraacetic acid (K2EDTA) or sodium oxalate (Na2C2O4), and (iii) with or without the addition of sodium fluoride (NaF). Spiked blood samples were stored at two different temperatures (4 and −20°C), analyzed after different storage times and after three freeze–thaw cycles. Opiate concentrations were decreased in all conditions, but the most unstable was 6‐acetyl‐morphine. The addition of NaF as preservative improved the stability of opiates at all conditions studied, whereas the type of anticoagulant did not affect the stability of opiates. It was concluded that blood samples should be stored at −20°C in glass tubes containing oxalate and NaF for maximum stability.